Synthesis, Physiochemical and Thermal Study of Some Transition Metal Complexes with Chelating Ligand and Study their Theoretical Treatments - Israa H. Ibraheem (Journal of Global Pharma Technology, 2018)
Complexes of Cr+3, Ni+2 and Cu+2 with the ligand 2-(p- nitrobenzoyl) thiobenzimidazol) (L) were prepared and characterized by FT-IR ,UV-Visible, TG analysis ,Atomic absorption spectroscopy , Molar conductivity and magnetic moments measurements .The general formula has been suggested for all the prepared complexes [Cr(L)2Cl2]Cl.4H2O, [Ni(L)2(H2O)2]Cl2.2H2O and [Cu(L)2(H2O)2]Cl2.2C2H5OH to be an octahedral geometry. A theoretical treatment of these compounds in gas phase was done using HyperChem.8.7 program. Semi –empirical PM3 method was performed to evaluate the ∆H° ƒ, ∆ Eb and ∆ET for all compounds, also vibration frequencies, electronic spectra and electrostatic potential HOMO and LUMO energies for the ligand was estimated to determine the reactive position for this ligand .Keywords: Physiochemical study, Transition metal ion, octahedral structure, Theoretical study.